Alterations in metabolome and microbiome: new clues on cathelicidin-related antimicrobial peptide alleviates acute ulcerative colitis - Jiang, Nan; Liu, Zhongyuan; Wang, Haiyang; Zhang, Lichun; Li, Mengjiao; Li, Gaoqian; Li, Chang; Wang, Bo; Zhao, Cuiqing; Liu, Liming (Frontiers in Microbiology, 2024)
Ulcerative colitis (UC) is a chronic and recurrent inflammatory disease of the gastrointestinal tract. This study aimed to determine the effect of cathelicidin-related antimicrobial peptide (Cramp) on dextran sulfate sodium (DSS)-induced acute experimental colitis in mice and to investigate the underlying mechanisms. Acute UC was induced in C57BL/6 mice with 3% DSS for 7 days, 4mg/kg b.w. synthetic Cramp peptide was administrated once daily starting on day 4 of the experimental period. Mice were evaluated for body weight, colon length, colon histopathology, and inflammatory cytokines in colon tissue. Using 16s rRNA sequencing, the composition structure of gut microbiota was characterized. Metabolomic profiling of the serum was performed. The results showed that DSS treatment significantly induced intestinal damage as reflected by disease activity index, histopathological features, and colon length, while Cramp treatment significantly prevented these trends. Meanwhile, Cramp treatment decreased the levels of inflammatory cytokines in both serum and colonic tissue on DSS-induced colitis. It was also observed that DSS damaged the integrity of the intestinal epithelial barrier, whereas Cramp also played a protective role by attenuating these deteriorated effects. Furthermore, Cramp treatment reversed the oxidative stress by increasing the antioxidant enzymes of GSH-PX and decreasing the oxidant content of MDA. Notably, compared to the DSS group, Cramp treatment significantly elevated the abundance of Verrucomicrobiota at the phylum level. Furthermore, at the genus level, Parasutterella and Mucispirllum abundance was increased significantly in response to Cramp treatment, although Roseburia and Enterorhabdus reduced remarkably. Metabolic pathway analysis of serum metabolomics showed that Cramp intervention can regulate various metabolic pathways such as α-linolenic acid, taurine and hypotaurine, sphingolipid, and arachidonic acid metabolism. The study concluded that Cramp significantly ameliorated DSS-induced colonic injury, colonic inflammation, and intestinal barrier dysfunction in mice. The underlying mechanism is closely related to the metabolic alterations derived from gut microbiota.